2022
DOI: 10.1182/bloodadvances.2021005385
|View full text |Cite
|
Sign up to set email alerts
|

Pretherapy metabolic tumor volume is associated with response to CD30 CAR T cells in Hodgkin lymphoma

Abstract: Our group has recently demonstrated that chimeric antigen receptor T-cell therapy targeting the CD30 antigen (CD30.CAR-T) is highly effective in patients with relapsed and refractory (r/r) classical Hodgkin lymphoma (cHL). Despite high rates of clinical response, relapses and progression were observed in a subset of patients. The objective of this study was to characterize clinical and correlative factors associated with progression-free survival (PFS) after CD30.CAR-T cell therapy. We evaluated correlatives i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…Wang et al reported that out of 18 patients who received CAR30 T-cells, the remission rate for PR and above was 67.0%, with a median PFS of 6.0 months [ 18 ]. Timothy J et al showed that the CR rate of patients receiving CAR30 T-cells was 67.0%, with a median PFS of 11 months [ 6 ]. Furthermore, our previous study have shown that the CR rate of patients received CAR30 T-cells followed by anti-PD-1 antibody maintenance was 77.8% in total of nine patients [ 5 ], with updated 2-year PFS of 44.4% with a median follow-up of 38.3 months (range, 0–63 months) (Additional file 1 : Figure S1), indicating novel strategies to improve the efficacy of CAR30 T-cells were needed.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al reported that out of 18 patients who received CAR30 T-cells, the remission rate for PR and above was 67.0%, with a median PFS of 6.0 months [ 18 ]. Timothy J et al showed that the CR rate of patients receiving CAR30 T-cells was 67.0%, with a median PFS of 11 months [ 6 ]. Furthermore, our previous study have shown that the CR rate of patients received CAR30 T-cells followed by anti-PD-1 antibody maintenance was 77.8% in total of nine patients [ 5 ], with updated 2-year PFS of 44.4% with a median follow-up of 38.3 months (range, 0–63 months) (Additional file 1 : Figure S1), indicating novel strategies to improve the efficacy of CAR30 T-cells were needed.…”
Section: Discussionmentioning
confidence: 99%
“…The ZUMA-2 trial reported a 24% increase in ongoing responses for patients with TB Lugano above the median ( 14 ). In CD30 CART of Hodgkin’s lymphoma, the PFS was 13.3 months longer if TB MTV was below 60 mL ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…The ZUMA-2 trial reported a 24% increase in ongoing responses for patients with TB Lugano above the median (14). In CD30 CART of Hodgkin's lymphoma, the PFS was 13.3 months longer if TB MTV was below 60 mL (17). Beyond trials, there have been reports on TB and impact on PFS and/or OS from retrospective studies that used commercial CART products.…”
Section: Discussionmentioning
confidence: 99%
“…In a clinical trial from China, 5 of 6 HL patients achieved CRs after the infusion of the thirdgeneration anti-CD30 CAR-T cells, and the long-term remission lasted over 24 months in 3 patients (45). In another phase 1/2 clinical trial, 27 patients were treated with the anti-CD30 CAR-T cells and 67% of patients achieved CRs within 6 weeks, but 63% of patients experienced disease progression with a median follow-up of 9.5 months (46). In addition, the expression of CD30 in HL was down-regulated after anti-CD30 CAR-T cell therapy (47).…”
Section: Targets For Car-t Cell Therapy In Hodgkin Lymphomamentioning
confidence: 99%